Mapping Of Nucleocapsid Protein (Np) Epitopes and Np-Phosphoprotein Interactive Domains of Newcastle Disease Virus with Np Monoclonal Antibodies - Ahmad Raus, Raha (2006)
The Newcastle disease virus (NDV) is an economically important poultry virus which replicates in certain human cancer cells. This virus contains a negative single stranded RNA genome which encodes for the nucleocapsid protein (NP), phosphorylated nucleocapsid-associated protein, phosphoprotein (P); matrix protein (M); fusion protein (F); haemaglutinin-neuraminidase protein (HN) and the RNA-directed RNA polymerase, large protein (L). The NP is the most abundant protein found in NDV. In this study, a panel of monoclonal antibodies (mAbs) against NP was developed to study the NP-P interactions in NDV. The spleen cells of Balb/C mice immunized with purified NP obtained from the velogenic NDV strain AF2240 were fused with myeloma cells (Sp2/0-Ag14 cell line). A panel of six mAbs were produced and characterized. Four of the mAbs secreted immunoglobulins from class IgG2a with kappa light chains and the remaining two were from class IgG1 with kappa light chains. Cross-reactivity test against the NPs from other six NDV strains showed that mAbs, a2, a2s and b2 cross-reacted with all NDV strains, while mAb b3 showed specificity towards the NP of strain AF2240, the strain that was used earlier to immunize the mice. The other two mAbs, b4s and c1, demonstrated cross-reactivity amongst the various viral strains with varying reactivities. These results indicate that certain epitopes recognized by the mAbs were well conserved in all NDV strains whilst the other epitopes may have undergone some structural changes. The antigenic sites of NP bound by the mAbs were localized by Western blot analysis. Four C- and N-terminally truncated NP mutants were purified from Escherichia coli, blotted to the nitrocellulose membrane and probed with NP mAbs. The results show that the antigenic sites bound by mAbs a2, a2s and b2 were located within amino acids 441 to 489 of the C-terminal of NP. On the other hand, antigenic sites that were recognized by the mAbs, b3 and b4s were located on the N-terminal half of NP from 26 to 121 amino acid residues. MAb c1 bound to all C- and N-truncated mutants indicating that the antigenic sites recognized by mAb c1 may be located within amino acids 122 to 375. One of the mAb, a2s was further used as a tool in protein-protein interaction study between assembled NP (NPNC) and P. The NPNC was purified from E. coli by ammonium sulphate precipitation and sucrose garadient. In determining the interaction regions of P that bind to NPNC, the mAb is used in immunoprecipitating the radioactively labeled Ps-NPNC complex. The failure of certain P deleted mutants to form complex with NPNC demonstrated that the regions of P which were deleted from those mutants were responsible with the binding to NPNC. After 18 different N- and C-terminally truncated P mutants were tested in the radioimmunoprecipitation assay, it showed that the region of P that binds to NPNC is located within the internal region of C-terminal half of P, from amino acids 243 to279. In agreement with the radioimmunoprecipitation results, protein binding assay, another assay that was carried out to determine the P-NPNC interactive domain also showed that the interactive domain was mapped to the internal region of the C-terminal half of P (amino acids 224-279). A slightly bigger region of interaction domain was determined by the latter assay compared to the former assay was due to its nature and higher sensitivity of the assay. Nevertheless, both assays showed that the N-terminal half and immediate C-terminal end of P is not involved in the binding of P to NPNC. To further explore the interactions between P and NP, Far Western blotting was carried out to determine the binding domain of P to NP monomer, NPO. The NPO was obtained by fractionating the NPNC in SDS-PAGE. In this assay, the same deleted mutants that are utilized in mapping P-NPNC interactive domain were also used. The assay showed that amino acids 224-279 were indispensable for the P-NPO binding. Interestingly, these were the same amino acids that were responsible for the P-NPNC interaction. These results indicate that these amino acids were crucial for interaction between P and NP and may play bigger roles in transcription and replication of viral genome.